If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 48 + -5x = 0 Solving 48 + -5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-48' to each side of the equation. 48 + -48 + -5x = 0 + -48 Combine like terms: 48 + -48 = 0 0 + -5x = 0 + -48 -5x = 0 + -48 Combine like terms: 0 + -48 = -48 -5x = -48 Divide each side by '-5'. x = 9.6 Simplifying x = 9.6
| x^3-x^2-x-4=0 | | s^3-s^2-s-4=0 | | 5t^2+9=234 | | 3t+9=t+13 | | 1+3(2x-7)=8-4(3x+1) | | 5(4+m)-3(3m-1)=-9 | | 3a+10=3a-4 | | 9ab^2+27a^3-27a^2b-b^3+c^3=0 | | 2z+6=36 | | 5p+9=4p+8 | | -2(6z-3)+13(z-7)=-81-9 | | 25x=4x^(1/3) | | 9s-8(s-10)+3=84 | | 3x+8y=59 | | -3(s-2)+4s=-11-2 | | 7(s-2)+4s=-11-2 | | 5(3x+8)+5x=5(2d+10)-36 | | 4(4b+6)=3(2b-18) | | y=150-s | | 4(3y-1)-2y=56 | | 3(2n-6)=4m-10 | | 9(m-1/3)=9 | | 13=145-11q | | 20=90-5q | | (y+2)-2(y+3)=4(x+1) | | 19=55-4p | | 12p+14=86 | | 111-9p=12 | | 5(x+2)-2(x+3)=4(x+1) | | 17=39-2p | | 6=72-11q | | 5y+6y-81=7x+102+65y |